PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERATING (Studi Empiris pada WP OP di KPP Pratama Singosari) - Moh. Ahbab Abdul Aziz; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research was conducted with the aim of: 1) To know the effect ofunderstanding taxation and risk preference rules on compliance compliance level ofindividual taxpayer in KPP Singosari. 2) To determine whether risk preference canmoderate the relationship between understanding tax regulations on compliance withindividual taxpayers in KPP Singosari. Independent variable in this study is theunderstanding of taxpayer regulation (X1). Dependent Variables in this study istaxpayer compliance (Y), Variables that strengthen or weaken the direct relationshipbetween independent variables and dependent variables in this study risk preferences(X2) used as a moderating variable.The population used in this study is WP OP in North Malang tax registered inKPP Pratama Singosari amounted to 73,621 taxpayers. This taxpayer consists ofcorporate taxpayers as many as 6,023 personal taxpayers as much as 67,598taxpayers individual taxpayers contained in the area of North Malang include: WPOP in Singosari, WP OP in Lawang, WP OP in Karang Ploso, WP OP In Dau.Sampling location is in North Malang region. Determination of samples in this studyusing sampling technique with Convenience Sampling. The method used in this studyusing the method of Moderated Regression Analysis (MRA).Based on the results of the analysis can be put forward several conclusions asfollows: 1) F test results show that the variables Zscore: Understanding of TaxpayerRegulations, Zscore: Risk Preferences and ABSX1_X2 simultaneously orsimultaneously affect taxpayer compliance. 1) T test results indicate that for thevariable Zscore: Understanding of the Regulation of Taxpayers partially has noeffect on taxpayer compliance. 2) Zscore: Risk Preferences partially affect taxpayercompliance. 3) risk preference variable can memoderating Understanding ofTaxpayer Regulation to taxpayer compliance.Keywords : Understanding of tax regulations, Taxpayer Compliance, RiskPreference